Uji FTIR dan uji fitokimia dari madu trigona spp. Untuk persiapan suplemen wanita prakonsepsi - -, Emmasitah; Raya, Indah; Usman, Andi Nilawati; Mauludiyah, Indah; Prihartini, Ade Rahayu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: This study aims to identify functional groups and chemical compounds using FTIR (Fourier Transform Infrared), phytochemical tests to identify the content of saponins, tannins, flavonoids, alkaloids, terpenoids and steroids using chemical solutions and total phenol test using 20D+ spectroscopy to determine the amount of polyphenols in Trigona spp. honey. This research is a laboratory study conducted at the Integrated Chemistry Laboratory and Biochemistry Laboratory, Faculty of Mathematics and Natural Sciences, Hasanuddin University Makassar. The sample used in the study was Trigona spp. honey which is a local livestock honey from Masamba, North Luwu regency, South Sulawesi, and has been processed by the Halal Center of Hasanuddin University Makassar.Results: Flavonoids and polyphenols were found in phytochemical tests using Pb(CH3COO)2 and FeCl3 reagents. The FTIR test results indicate the presence of phenolic structures included in the flavonoid group. The total phenolic results from the total phenol test on Trigona spp. honey samples. The amount of polyphenols was 0.28%.Conclusion: This study concluded that there are flavonoids and polyphenols in honey Trigona spp. with a total phenol of 0.28%. Trigona spp. honey has antioxidant effects, so it is well used as a complementary therapeutic supplement for preconception women for handling reproductive health problems.